Influence of the Drilling Parameters in the Single-Lip Deep-Hole Drilling Process on the Surface Integrity of Nickel-Based Alloy - Tao Wu; Fangchao Zhang; Haoguang Zhou; Dong Zhang (Machines)
Single-lip deep-hole drilling is a key technology for the precision machining of high-temperature nickel-based alloy pore structures in aero engines. However, the intense thermo-mechanical coupling effects during machining can easily lead to surface integrity deterioration, and the correlation mechanism between microstructure and properties remains unclear. By adjusting the spindle speed and feed rate, a series of orthogonal experiments were carried out to study the integrity characteristics of the machined surface, including surface morphology, roughness, work hardening, and subsurface microstructure. The results reveal gradient structural features along radial depth: a dynamic recrystallized layer (RL) at the surface and a plastically deformed layer (PDL) containing high-density subgrains/distorted grains in the subsurface. With the increase in the spindle speed, the recrystallization phenomenon is intensified, the RL ratio of the machined-affected zone (MAZ) is increased, and the surface roughness is reduced to ~0.5 μm. However, excessive heat input will reduce the nanohardness. Low feed rates (<0.012 mm/rev) effectively suppress pit defects, whereas high feed rates (≥0.014 mm/rev) trigger pit density resurgence through shear instability. Progressive material removal rate (MRR) elevation drives concurrent PDL thickness reduction and RL proportion growth. Optimal medium MRR range (280–380 mm3/min) achieves synergistic RL/PDL optimization, reducing machining-affected zone thickness (MAZ < 35 μm) while maintaining fatigue resistance. These findings establish theoretical foundations for balancing efficiency and precision in aerospace high-temperature component manufacturing.